Biochemical Markers for Determining Vulnerable Atherosclerotic Plaque in Stenotic Patient: Biochemical Markers Study of Myeloperoxidase (MPO), Matrix Metallo-Proteinase-9 (MMP-9), Secretory Phospholipase A2 (SPLA2) and CD40 Ligand - Tommy Heryantho; Andi Wijaya; Teguh Santoso (The Indonesian Biomedical Journal, 2009)
BACKGROUND: Thrombus is a main cause of cardiac death. Therefore identifying which coronary artery plaque is vulnerable to rupture is a critical step for cardiac intervention to prevent future cardiac events. Systemic biochemical markers are used for predicting rupture of coronary plaque or identifying stenotic coronary artery plaque(s) vulnerable to rupture.METHODS: Blood samples of 2x24 locations (2x10 controls, 2x12 stable plaques and 2x2 unstable plaques) of 13 patients to undergo stent placement were taken from an artery which showed no stenosis (control), 70% or more stenosis of stable plaques and unstable plaques, respectively. The blood samples were taken by using microcatheter distally and proximally. Concentrations of MPO, MMP-9, SPLA2 and CD40L of each sample were assayed.RESULTS: Concentration of MMP-9 in unstable coronary artery plaque (94.7+14.4 ng/ml) significantly increased compared with that of stable coronary artery plaque (71.0+67.8 ng/ml, p=0.024). SPLA2 concentration significantly decreased in unstable coronary artery plaque (45.9+14.0 pg/ml) compared with that of stable coronary artery plaque (80.9+39.3 pg/ml, p=0.015). Nine of ten studied subjects showed an average of 14.5% (range: 0.0-28.8%) decrease of the SPLA2 concentration in stable plaques compared with that of the non-stenotic coronary artery.CONCLUSION: MMP-9 increased in unstable coronary artery plaque compared with that of stable coronary plaque. Unstable coronary artery plaques absorbed SPLA2 from the vasculars more than the stable plaques and control plaques. MMP-9 and SPLA2 may be used as markers of stability of a plaque in coronary artery in relation to its rupture potential.KEYWORDS: stable and unstable plaque, myeloperoxidase, matrix metalloproteinase-9, secretory phospholipase A2, CD40 Ligand